1996
DOI: 10.1111/j.1476-5381.1996.tb15518.x
|View full text |Cite
|
Sign up to set email alerts
|

GABA, glutamate and substance P‐like immunoreactivity release: effects of novel GABAB antagonists

Abstract: 1 The effects of various GABA receptor ligands on the electrically-evoked release of endogenous GABA, glutamate and substance P-like immunoreactivity from the dorsal horn of rat isolated spinal cord were examined. 2 Exogenous GABA (10-300 pM) significantly decreased the evoked, but not basal, release of endogenous glutamate in a concentration-dependent manner. The GABAA agonist, isoguvacine (1-100 gM), failed to decrease the release of glutamate although it did reduce the release of GABA.Baclofen (0.1 -1I000 M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(27 citation statements)
references
References 56 publications
1
26
0
Order By: Relevance
“…L689,560, a high-affinity NMDA/glycine-site antagonist (Stauch Slusher et al, 1994) and HA-966 (Javitt et al, 2000), a partial agonist, were used to evaluate involvement of NMDA receptors in GTI-induced effects. The GABA B agonist baclofen, and antagonists phaclofen (Kerr et al, 1987) and CGP52432 (Teoh et al, 1996) were used to evaluate potential GABA B receptor involvement.…”
Section: Resultsmentioning
confidence: 99%
“…L689,560, a high-affinity NMDA/glycine-site antagonist (Stauch Slusher et al, 1994) and HA-966 (Javitt et al, 2000), a partial agonist, were used to evaluate involvement of NMDA receptors in GTI-induced effects. The GABA B agonist baclofen, and antagonists phaclofen (Kerr et al, 1987) and CGP52432 (Teoh et al, 1996) were used to evaluate potential GABA B receptor involvement.…”
Section: Resultsmentioning
confidence: 99%
“…Whilst it is di cult to make direct comparisons between the data presented here and that generated using baclofen or 3-APPA to activate GABA B receptors, it is interesting that our data for both pre-and postsynaptic GABA B receptors at GABA-mediated synapses ®t best with a subtype that is sensitive to all three antagonists mentioned above and, therefore, suggest that these receptors are similar to those that control the cortical release of somatostatin but not GABA or glutamate (Bonanno & Raiteri, 1993b). However, the subclassi®cation of GABA B receptors suggested by Bonanno & Raiteri (1993b) is not universally accepted, most notably because their observations have not been repeated by others using electrically stimulated release in cortical and dorsal horn slices (Waldmeier et al, 1994;Teoh et al, 1996). In fact, quantitative pharmacological analysis of the antagonism of baclofen-induced inhibition of electrically-induced GABA and glutamate release revealed that K D values for GABA B receptor antagonists were similar to those calculated from radioligand binding studies in the same laboratories (Waldmeier et al, 1994), a situation echoed using electrophysiological approaches in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these data and the premise that radioligand binding does not discriminate between pre-and post-synaptic GABA B receptors it was proposed that either (a) each antagonist does not di erentiate between possible GABA B receptor subtypes or (b) all antagonists are speci®c for a particular GABA B receptor subtype and that compounds that activate/antagonize other GABA B receptor subtypes have yet to be developed. That said, in the dorsal horn CGP 56999A potently antagonized GABA B receptors controlling the release of GABA and substance P without a ecting those which regulate the release of glutamate (Teoh et al, 1996) raising the possibility that pharmacologically distinguishable GABA B receptors do exist in the CNS. If so, it is unlikely that it will be possible to allocate a particular pharmacological subtype to the GABA B heteroreceptor on glutamate terminals, another to the heteroreceptor on somatostatin terminals, another to the GABA B autoreceptor and so on.…”
Section: Discussionmentioning
confidence: 99%
“…Differences between presynaptic auto-and heteroreceptors in the CA3 area of the hippocampus included the finding that GABA A receptor-mediated synaptic inhibition was more sensitive to baclofen (Lei and McBain, 2003) and to pertussis toxin and barium treatments (Thompson and Gahwiler, 1992). In measuring GABA, Glu, and other neurotransmitter release, several agonists and antagonists displayed pharmacologically distinct potencies between the presynaptic GABA B auto-and heterosynaptic receptors (Bonanno and Raiteri, 1993;Teoh et al, 1996;Bonanno et al, 1997). Now, for the first time, in the hippocampal CA1 area, we have demonstrated that the novel GABA B receptor-positive allosteric modulator, CGP7930, selectively potentiated baclofen-induced activation of presynaptic autoreceptors.…”
Section: Discussionmentioning
confidence: 99%